A history of Old English verse layout : poetics on the page - Burns, Rachel A. (Arc Humanities Press, 2024)
This study presents the first full history of Old English poetic mise-en-page, drawing its approach from the fields of literary criticism, art history, metrics, palaeography, and the history of the book. Paying special attention to lineation, this book surveys the layout of poetry from the earliest Latin writings in England, to modern editions of the twentieth and twenty-first centuries.
Keywords: English poetry -- Old English, ca. 450-1100 -- History and criticism.; English language -- Old English, ca. 450-1100 -- Versification.; Poésie anglaise -- ca 450-1100 (Vieil anglais) -- Histoire et critique.; Anglais (Langue) -- ca 450-1100 (Vieil anglais) -- Versification.; LITERARY CRITICISM / Medieval.